Reporting challenges facing the Solomon Islands Ministry of Fisheries & Marine Resources - Brown, Alistair (Elsevier, 2016)
This study uses textual analysis of the audit reports of the Office of the Auditor General of Solomon Islands to determine the reporting compliance of the Solomon Islands Ministry of Fisheries & Marine Resources (MFMR) for the period 2001–2013. The results of the study show that the MFMR faces considerable reporting challenges in the areas of internal control systems, recording and documentation. The study puts forward a number of ideas how the Ministry might meet these challenges to stem ongoing losses of fishing revenue for the national economy.